2021
DOI: 10.1111/hiv.13179
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in cancer incidence in Australian people living with HIV between 1982 and 2012

Abstract: Objectives:The aim of the study was to describe time trends in cancer incidence in people living with HIV (PLHIV) in Australia between 1982 and 2012. Methods:A population-based prospective study was conducted using data linkage between the national HIV and cancer registries. Invasive cancers identified in PLHIV were grouped into AIDS-defining cancers (ADCs), infection-related non-ADCs (NADCs), and non-infection-related NADCs. Crude and age-standardized incidence rates of cancers were calculated and compared ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Indeed, an analysis of cancers overall in this identical Australian cohort identified substantially higher rates of many cancers, particularly NHL, HL, KS, and anal and liver cancers, compared with those in the general population. 5 In our study, the incidence of SPC overall in PLWHIV did not significantly change between 1982 and 2012. The most common SPCs were non-Hodgkin lymphoma (mostly diffuse large B-cell lymphoma), KS, and anal cancer.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Indeed, an analysis of cancers overall in this identical Australian cohort identified substantially higher rates of many cancers, particularly NHL, HL, KS, and anal and liver cancers, compared with those in the general population. 5 In our study, the incidence of SPC overall in PLWHIV did not significantly change between 1982 and 2012. The most common SPCs were non-Hodgkin lymphoma (mostly diffuse large B-cell lymphoma), KS, and anal cancer.…”
Section: Discussionmentioning
confidence: 44%
“…Indeed, an analysis of cancers overall in this identical Australian cohort identified substantially higher rates of many cancers, particularly NHL, HL, KS, and anal and liver cancers, compared with those in the general population. 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the incidence of non-AIDS-related cancers rise in HIV-infected patients in Western countries [ 24 , 25 ]. More recent data from studies of HIV-infected people in the US, Europe and Australia indicated that non-AIDS-related cancers increased, reflecting increasing rates in the general population [ 26 , 27 ]. In developing countries, including China, there are a large proportion of newly-HIV infected people, AIDS-related cancers are the most common malignances [ 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer incidence and burden (ie, the number of new cases) among PLWH is strongly influenced by the characteristics of the population living with HIV (eg, demographics, co‐infections, co‐morbidities), availability of timely ART and access to health care—all factors that differ across countries and regions of the world, and over time. The types of cancer that occur at higher rates among PLWH are largely consistent across countries and are typically caused by oncogenic viruses 4‐8 . However, rates of KS, cervical and conjunctival cancer remain much higher in sub‐Saharan Africa (SSA) than in Europe, Latin America and North America (Figure 1).…”
Section: International Patterns In Cancer Incidencementioning
confidence: 99%